1993
DOI: 10.1111/j.1751-0813.1993.tb03306.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of injectable and pour‐on formulations of moxidectin against lice on cattle

Abstract: The efficacy of one administration of moxidectin against natural infestations of the 3 common species of cattle lice in Australia: Linognathus vituli, Damalinia bovis and Haematopinus eurysternus, was determined. A high degree of control of L vituli (the long-nosed sucking louse) was achieved with both the cattle injection (96.7% and 100%) at 0.2 mg/kg and the cattle pour-on formulation (94.6% and 100%) at 0.5 mg/kg on the 2 farms where this louse occurred. An injection of moxidectin at 0.2 mg/kg did not elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…It differs from ivermectin in chemistry, structure and potency, and is effective against nematode and arthropod parasites (Williams et al, 1922;Craig et al, 1992;Chick et al, 1993;Doherty et al, 1994;Kieran, 1994). The low toxicity of moxidectin to dung-breeding Coleoptera has been recorded by Fincher & Wang (1992) who found that dung from moxidectin-treated cattle had no effects on brood ball production or adult emergence in Euomhcellus intermedius (Reiche) and Onthophagus gazella.…”
Section: Discussionmentioning
confidence: 93%
“…It differs from ivermectin in chemistry, structure and potency, and is effective against nematode and arthropod parasites (Williams et al, 1922;Craig et al, 1992;Chick et al, 1993;Doherty et al, 1994;Kieran, 1994). The low toxicity of moxidectin to dung-breeding Coleoptera has been recorded by Fincher & Wang (1992) who found that dung from moxidectin-treated cattle had no effects on brood ball production or adult emergence in Euomhcellus intermedius (Reiche) and Onthophagus gazella.…”
Section: Discussionmentioning
confidence: 93%
“…18,25 In contrast OPs have inconsistent performance against B bovis, the efficacy ranging from 73 to 100%. 17,18 Similarly MLs given parenterally have efficacies ranging from 0 to 100%, [19][20][21][22][23] most commonly in the 80 to 90% range. Topically applied MLs have better efficacy than parenterally administered MLs (84 to 100%) [22][23][24] but are still less effective than synthetic pyrethroids.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Similarly MLs given parenterally have efficacies ranging from 0 to 100%, [19][20][21][22][23] most commonly in the 80 to 90% range. Topically applied MLs have better efficacy than parenterally administered MLs (84 to 100%) [22][23][24] but are still less effective than synthetic pyrethroids. Deltamethrin and MLs are very effective against H eurysternus 1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21]25 as was zeta-cypermethrin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…También la moxidectina inyectable es eficiente para el control de piojos chupadores (99-100%), contra Haematopinus euryternus, Linognathus vituli y Solenoptes capillatus y miasis bovina (Hypoderma lineatum). Sin embargo, la formulación "pour-on" proporciona mejor control de piojos mordedores (Damalinia bovis) que la formulación inyectable (37). Lonneux y Losson (36) demostraron que la moxidectina "pour on" (0.5 mg/kg p.v.)…”
Section: Ectoparásitosunclassified